PKM Pemberdayaan Masyarakat Penerima Makanan Bergizi Gratis Melalui Komunikasi Sosial Untuk Meningkatkan Pemenuhan Gizi Nasional Di Desa Adidharma Kabupaten Cirebon: Penelitian - Suswati, Elis; Mustain, Iing; Herlina, Yeyen (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Nutritional problems remain a crucial issue in human development in Indonesia, including in Cirebon Regency, which recorded a stunting prevalence of 22.9 percent. This condition is exacerbated by the community’s low level of knowledge regarding balanced nutrition and their limited ability to optimize the use of nutritious food assistance. This Community Service Program (Pengabdian kepada Masyarakat / PkM) aims to empower beneficiaries of the Free Nutritious Meal Program (MBG) in Adidharma Village, Cirebon Regency through a social communication approach as a strategy to enhance nutritional literacy and promote healthy behavior changes. The program was implemented using the Participatory Action Research (PAR) method involving 60 participants consisting of posyandu cadres and MBG beneficiaries. The series of activities included social communication training, nutrition and hygiene education, local nutritious food processing practice, application of digital educational media, and three months of community mentoring. Data were collected through observation, interviews, and pre-test/post-test, then analyzed descriptively both qualitatively and quantitatively. The results indicated a significant increase in participants’ knowledge of balanced nutrition from 62% to 87% and communication skills from 55% to 85%. Moreover, posyandu activities became more interactive, the community began adopting healthier eating patterns, and local nutrition cadres were formed as agents of change. The innovation of using digital media such as WhatsApp Groups, educational videos, and visual nutrition modules proved effective in expanding educational outreach. Overall, this program contributed to improving cadre capacity, changing community nutrition behavior, and strengthening community self-reliance in fulfilling family nutrition. This PkM also supports the achievement of the Sustainable Development Goals (SDGs) number 2 (Zero Hunger) and number 3 (Good Health and Well-being) through a participatory and sustainable social communication approach.